Salmonellosis in persons infected with human immunodeficiency virus: a report of seven cases from Malaysia - Puthucheary, S.D.; Ng, K.P.; Hafeez, A.; Raja, N.S.; Hassan, H. (Seameo Regional Tropical Medicine & Public Health, 2004)
Persons infected with human immunodeficiency virus (HIV) have an increased risk of salmonellosis when compared to the general population. We describe seven such patients with Salmonella bacteremia, of whom two had recurrent salmonellosis. In the latter two cases the infection was unusually severe, characterized by widespread infection, bacteremia and relapse, despite standard antimicrobial therapy. HIV-infected individuals will benefit from education on the source of Salmonella, mode of acquisition and prevention through safe food handling and food preparation practices. Because of the difficulty of eradicating Salmonella infection in patients with acquired immunodeficiency syndrome, long-term suppressive treatment with antimicrobials is warranted.